Rural Entrepreneurs in the Local Society - Ольга Петровна Фадеева (Journal of Economic Sociology, 2010)
The author addresses to the study of the embeddedness of the new economic subjects in the villages, their place in the social structure and the relation problem with the local people, authorities, big collective farms and other business partners and competitors. The author tries to analyze to what extent the rural area with its traditions and stereotypes, relatively poor population and weaker market structure was favorable to the appearance of new effective owners; what rigidities this infrastructure put on their development and to what extent it influenced the specifics of the modern rural entrepreneurship. The empirical base for the survey was the data of the sociological questionnaire of the rural entrepreneurs of the Novosibirsk region, which was held by the employees of the department for social problems of the Institute of Economics RAS in 2000-2001.